2014
DOI: 10.1007/s10482-014-0170-z
|View full text |Cite
|
Sign up to set email alerts
|

On the reclassification of species assigned to Candida and other anamorphic ascomycetous yeast genera based on phylogenetic circumscription

Abstract: Multigene phylogenies have been instrumental in revising the classification of ascosporic (teleomorph) yeasts in a natural system based on lines of descent. Although many taxonomic changes have already been implemented for teleomorph taxa, this is not yet the case for the large genus Candida and smaller anascosporic (anamorph) genera. In view of the recently introduced requirement that a fungal species or higher taxon be assigned only a single valid name under the new International Code of Nomenclature for alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 134 publications
1
90
0
Order By: Relevance
“…In addition to proposing two novel species of the Yamadazyma and Zygoascus clades, we also propose the reassignment of the five known species Candida olivae, Candida takamatsuzukensis, Candida tumulicola, Candida polysorbophila and Candida bituminiphila to the genus Yamadazyma or Zygoascus as new combinations. Our transfer of these five species to the genera Yamadazyma and Zygoascus is consistent with the placement suggested by Daniel et al (2014). Reclassifications of other species of Candida shown in the trees may be made according to the 'one fungus5one name' principle of the current International Code of Nomenclature of Algae, Fungi, and Plants (Melbourne Code) (McNeill et al, 2012; Norvell, 2011).…”
Section: Identification and Taxonomysupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to proposing two novel species of the Yamadazyma and Zygoascus clades, we also propose the reassignment of the five known species Candida olivae, Candida takamatsuzukensis, Candida tumulicola, Candida polysorbophila and Candida bituminiphila to the genus Yamadazyma or Zygoascus as new combinations. Our transfer of these five species to the genera Yamadazyma and Zygoascus is consistent with the placement suggested by Daniel et al (2014). Reclassifications of other species of Candida shown in the trees may be made according to the 'one fungus5one name' principle of the current International Code of Nomenclature of Algae, Fungi, and Plants (Melbourne Code) (McNeill et al, 2012; Norvell, 2011).…”
Section: Identification and Taxonomysupporting
confidence: 83%
“…Species of the C. membranifaciens clade have been suggested to be assigned to the genus Yamadazyma (Daniel et al, 2014). On the other hand, two isolates placed in the Zygoascus clade (Kurtzman & Robnett, 2007) were also found among the minority yeast isolates from both tumuli.…”
Section: Novel Species and Combinations In Yamadazyma And Zygoascusmentioning
confidence: 99%
“…With the availability of rapidly expanding public sequence databases and DNA sequencing facilities, it is now possible to process a large number of samples within a week. Indeed, coupled with the development of efficient yeast species identification has been a rapid increase in the number of published new yeast species, species name revisions, and a wealth of their ecological data over the last decade (Kurtzman et al 2011;Daniel et al 2014).…”
Section: A Brief History Of Dna Sequence-based Fungal Identificationmentioning
confidence: 99%
“…As C. magnoliae, C. sorbosivorans and C. vaccinii had been placed in the Starmerella clade of Saccharomycotina by previous D1/D2 analyses Daniel et al 2014), the close relationship revealed among their D1/D2 sequences and that of the Syrian isolates suggested that the latter can also be assigned to this group. Because of this relationship, the name Starmerella syriaca f.a., sp.…”
Section: Resultsmentioning
confidence: 83%
“…The Starmerella clade includes yeasts predominantly isolated from bees and their environment (reviewed in Rosa et al 2003, Daniel et al 2014. As bees visit flowers, members of the clade can frequently be encountered in flowers (e.g.…”
Section: Resultsmentioning
confidence: 99%